(untitled) - Zahner, L William (Hoboken, NJ., 2005)
Architectural Metal Surfaces demonstrates techniques for achieving a variety of surface effects through the application of texture, color treatments, and lighting effects: Presents more than 150 illustrations. Helps develop realistic expectations and accurate specifications and details. Describes the durability and maintenance requirements of various finishes.
Keywords: Metals,Architectural metal-work; Surfaces